“One less thing to worry about”: Barriers and facilitators of PrEP uptake among MSM in Karachi, Pakistan: A qualitative study - Batool Fatima; Sarmad Soomar; Preet Katyara; Shariqa Batool; Syed Faisal Mahmood (PLOS Global Public Health, 2026)
In Pakistan, MSM represent one of the key populations at risk of HIV, with rising rates of HIV compared to the general population and other key populations. Pre-exposure prophylaxis (PrEP) was rolled out in Pakistan in two of the most populated provinces, Sindh and Punjab, targeting key populations including MSM. However, only 23% of the high-risk population in Sindh and only 9% in Punjab used PrEP. A qualitative study with a descriptive exploratory design was conducted to explore the barriers, willingness, and preferred ways of using PrEP among Men who have Sex with Men (MSM) in Karachi, Sindh. In-depth interviews were conducted with six MSM in the outpatient setting of a tertiary care hospital in Karachi, where PrEP is prescribed and available for use in the MSM population. Participants reported lack of awareness, fear of stigma and discrimination, concerns about privacy and confidentiality, and financial and logistical challenges as barriers to their willingness and uptake of PrEP. Facilitators included awareness, accessibility, and availability of PrEP; perceived benefits of PrEP; affordability; social support; and experiences of professionalism and non-judgmental care in PrEP services. Participants recommended raising awareness at MSM social gatherings or on MSM dating applications such as Grindr, ensuring privacy, anonymity, and comfort by providing online consulting services and male care providers, the possibility of home testing and delivery of PrEP medication, and the need for emotional support and validation of concerns when needed. They also expressed a desire for PrEP with a longer shelf life or long-acting injections. This study provides insights into the enabling factors and roadblocks in the uptake of PrEP among MSM and provides an opportunity to refine Human Immunodeficiency Virus (HIV) prevention services.